Addition of triple negativity of breast cancer as an indicator for germline mutations in predisposing genes increases sensitivity of clinical selection criteria - Hoyer, Juliane; Vasileiou, Georgia; Uebe, Steffen; Wunderle, Marius; Kraus, Cornelia; Fasching, Peter; Thiel, Christian; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; Reis, André (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common cancer in women. 12-15% of all tumors are triple-negative breast cancers (TNBC). So far, TNBC has been mainly associated with mutations in BRCA1. The presence of other predisposing genes seems likely since DNA damage repair is a complex process that involves several genes. Therefore we investigated if mutations in other genes are involved in cancer development and whether TNBC is an additional indicator of mutational status besides family history and age of onset. METHODS: We performed a germline panel-based screening of 10 high and low-moderate penetrance breast cancer susceptibility genes (BRCA1, BRCA2, ATM, CDH1, CHEK2, NBN, PALB2, RAD51C, RAD51D and TP53) in 229 consecutive individuals affected with TNBC unselected for age, family history or bilateral disease. Within this cohort we compared the number of mutation carriers fulfilling clinical selection criteria with the total number of carriers identified. RESULTS: Age at diagnosis ranged from 23 to 80 years with an average age of 50.2 years. In 57 women (24.9%) we detected a pathogenic mutation, with a higher frequency (29.7%) in the group manifesting cancer before 60 years. Deleterious BRCA1 mutations occurred in 14.8% of TNBC patients. These were predominantly recurrent frameshift mutations (24/34, 70.6%). Deleterious BRCA2 mutations occurred in 5.7% of patients, all but one (c.1813dupA) being unique. While no mutations were found in CDH1 and TP53, 10 mutations were detected in one of the six other predisposition genes. Remarkably, neither of the ATM, RAD51D, CHEK2 and PALB2 mutation carriers had a family history. Furthermore, patients with non-BRCA1/2 mutations were not significantly younger than mutation negative women (p = 0.3341). Most importantly, among the 57 mutation carriers, ten (17.5%) would be missed using current clinical testing criteria including five (8%) with BRCA1/2 mutations. CONCLUSIONS: In summary, our data confirm and expand previous studies of a high frequency of germline mutations in genes associated with ineffective repair of DNA damage in women with TNBCs. Neither age of onset, contralateral disease nor family history were able to discern all mutation positive individuals. Therefore, TNBC should be considered as an additional criterion for panel based genetic testing.
EVALuna2:34811

Biallelic SEMA3A defects cause a novel type of syndromic short stature - Hofmann, Kristin; Zweier, Markus; Sticht, Heinrich; Zweier, Christiane; Wittmann, Wolfgang; Hoyer, Juliane; Uebe, Steffen; Van Haeringen, Arie; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Rauch, Anita (American Journal of Medical Genetics Part A, 2013)
Chromosomal microarray testing is commonly used to identify disease causing de novo copy number variants in patients with developmental delay and multiple congenital anomalies. In such a patient we now observed an 150 kb deletion on chromosome 7q21.11 affecting the first exon of the axon guidance molecule gene SEMA3A (sema domain, immunoglobulin domain (Ig), short basic domain, secreted, (semaphorin) 3A). This deletion was inherited from the healthy father, but considering the function of SEMA3A and phenotypic similarity to the knock-out mice, we still assumed a pathogenic relevance and tested for a recessive second defect. Sequencing of SEMA3A in the patient indeed revealed the de novo in-frame mutation p.Phe316_Lys317delinsThrSerSerAsnGlu. Cloning of the mutated allele in combination with two informative SNPs confirmed compound heterozygosity in the patient. While the altered protein structure was predicted to be benign, aberrant splicing resulting in a premature stop codon was proven by RT-PCR to occur in about half of the transcripts from this allele. Expression profiling in human fetal and adult cDNA panels, confirmed a high expression of SEMA3A in all brain regions as well as in adult and fetal heart and fetal skeletal muscle. Normal intellectual development in the patient was surprising but may be explained by the remaining 20% of SEMA3A expression level demonstrated by quantitative RT-PCR. We therefore report a novel autosomal recessive syndrome characterized by postnatal short stature with relative macrocephaly, camptodactyly, septal heart defect and several minor anomalies caused by biallelic mutations in SEMA3A.
EVALuna2:9194

BRCA mutations and their influence on pathological complete response and prognosis in a clinical cohort of neoadjuvantly treated breast cancer patients - Wunderle, Marius; Gaß, Paul; Häberle, Lothar; Flesch, Vivien M.; Rauh, Claudia; Bani, Mayada; Hack, Carolin; Schrauder, Michael G.; Jud, Sebastian; Emons, Julius; Erber, Ramona; Ekici, Arif Bülent; et al. (Breast Cancer Research and Treatment, 2018)
PURPOSE: BRCA1/2 mutations influence the molecular characteristics and the effects of systemic treatment of breast cancer. This study investigates the impact of germline BRCA1/2 mutations on pathological complete response and prognosis in patients receiving neoadjuvant systemic chemotherapy. METHODS: Breast cancer patients were tested for a BRCA1/2 mutation in clinical routine work and were treated with anthracycline-based or platinum-based neoadjuvant chemotherapy between 1997 and 2015. These patients were identified in the tumor registry of the Breast Center of the University of Erlangen (Germany). Logistic regression and Cox regression analyses were performed to investigate the associations between BRCA1/2 mutation status, pathological complete response, disease-free survival, and overall survival. RESULTS: Among 355 patients, 59 had a mutation in BRCA1 or in BRCA2 (16.6%), 43 in BRCA1 (12.1%), and 16 in BRCA2 (4.5%). Pathological complete response defined as "ypT0; ypN0" was observed in 54.3% of BRCA1/2 mutation carriers, but only in 22.6% of non-carriers. The adjusted odds ratio was 2.48 (95% CI 1.26-4.91) for BRCA1/2 carriers versus non-carriers. Patients who achieved a pathological complete response had better disease-free survival and overall survival rates compared with those who did not achieve a pathological complete response, regardless of BRCA1/2 mutation status. CONCLUSIONS: BRCA1/2 mutation status leads to better responses to neoadjuvant chemotherapy in breast cancer. Pathological complete response is the main predictor of disease-free survival and overall survival, independently of BRCA1/2 mutation status.
EVALuna2:34606

Breast MRI texture analysis for prediction of BRCA-associated genetic risk - Vasileiou, Georgia; Costa, Maria J.; Long, Christopher; Wetzler, Iris; Hoyer, Juliane; Kraus, Cornelia; Popp, Bernt; Emons, Julius; Wunderle, Marius; Wenkel, Evelyn; Uder, Michael; Beckmann, Matthias; et al. (BMC Medical Imaging, 2020)
BACKGROUND: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. METHODS: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty five controls were included. From each MRI 4225 computer-extracted voxels were analyzed. Non-imaging features including clinical, family cancer history variables and triple negative receptor status (TNBC) were complementarily used. Lasso-principal component regression (L-PCR) analysis was implemented to compare the predictive performance, assessed as area under the curve (AUC), when imaging features were used, and lasso logistic regression or conventional logistic regression for the remaining analyses. RESULTS: Lasso-selected imaging principal components showed the highest predictive value (AUC 0.86), surpassing family cancer history. Clinical variables comprising age at disease onset and bilateral breast cancer yielded a relatively poor AUC ( 0.56). Combination of imaging with the non-imaging variables led to an improvement of predictive performance in all analyses, with TNBC along with the imaging components yielding the highest AUC (0.94). Replacing family history variables with imaging components yielded an improvement of classification performance of 4%, suggesting that imaging compensates the predictive information arising from family cancer structure. CONCLUSIONS: The L-PCR model uncovered evidence for the utility of MRI texture features in distinguishing between BRCA1/2 positive and negative high-risk breast cancer individuals, which may suggest value to diagnostic routine. Integration of computer-extracted texture analysis from MRI modalities in prediction models and inclusion criteria might play a role in reducing false positives or missed cases especially when established risk variables such as family history are missing.
CRIS-Team Scopus Importer:2020-08-07
Keywords: BRCA1/2; Breast cancer; HBOC; L-PCR; MRI; Texture analysis

Calculating Future 10-Year Breast Cancer Risks in Risk-Adapted Surveillance: A Method Comparison and Application in Clinical Practice - Zachariae, Silke; Quante, Anne S.; Kiechle, Marion; Rhiem, Kerstin; Fehm, Tanja N.; Schröder, Jörg Gunther; Horvath, Judit; Leinert, Elena; Dikow, Nicola; Ronez, Joelle; Schönfeld, Mirjam; van Mackelenbergh, Marion T.; et al. (CANCER PREV RES, 2025)
The German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC) has successfully implemented risk-adapted breast cancer surveillance for women at high breast cancer risk in Germany. Women with a family history of breast and ovarian cancer but without pathogenic germline variants in recognized breast cancer risk genes are recommended annual breast imaging if their predicted 10-year breast cancer risk is 5% or higher, using the Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA) breast cancer risk model, as outlined in the current GC-HBOC guideline. However, women who initially do not meet this risk threshold may do so later, even if there is no new cancer in their family. To determine when this threshold is crossed, one could annually repeat BOADICEA calculations using an aging pedigree: the “prediction by aging pedigree” (AP) approach. Alternatively, we propose a simplified and more practical “’conditional probability” (CP) approach, which calculates future risks based on the initial BOADICEA assessment. Using data from 6,661 women registered with GC-HBOC, both methods were compared. Initially, 74% of women, ages 30 to 48 years, had a 10-year breast cancer risk below 5%, but 53% exceeded this threshold at an older age based on the AP approach. Among the women with an initial risk below the threshold, the CP approach revealed that 99% of women exceeded the 5% threshold at the same or an earlier age compared with the AP approach (88% of cases were within the same year or 1 year earlier). The CP approach has been implemented as a user-friendly web application. Prevention Relevance: The German Consortium for Hereditary Breast Cancer recommends annual breast imaging for women if their 10-year breast cancer risk is 5% or higher. Women who initially do not meet this risk threshold may do so later. We propose a simple method to determine future risks based on initial risk assessments.
CRIS-Team Scopus Importer:2025-02-28

Central nervous system anomalies in two females with Borjeson-Forssman-Lehmann syndrome - Kasper, Burkhard; Dörfler, Arnd; Di Donato, Nataliya; Kasper, Ekkehard M.; Wieczorek, Dagmar; Hoyer, Juliane; Zweier, Christiane (Epilepsy and Behavior, 2017)
Borjeson-Forssman-Lehmann syndrome (BFLS) is a rare disorder caused by mutations in the PHF6 gene. It manifests as syndromic X-linked recessive intellectual disability (ID) in males and as sporadic ID due to de novo mutations in females. Clinical features include variable ID and a range of somatic manifestations constituting a distinct phenotype in both males and females, respectively, including seizures in a few. Central nervous system (CNS) imaging data are largely unavailable for BFLS. Here we report on CNS MRI findings from two female individuals with BFLS due to a de novo duplication in PHF6 who presented with typical BFLS and epilepsy. Brain findings encompass an intriguing combination of structural abnormalities including a simplified gyral pattern and aspects resembling subcortical band heterotopia as signs of malformation of cortical development (MCD). This finding is of note, since PHF6 has been suggested to play pivotal roles in CNS development including neuronal migration.
EVALuna2:9368

Childhood cancer predisposition syndromes-A concise review and recommendations by the Cancer Predisposition Working Group of the Society for Pediatric Oncology and Hematology - Ripperger, Tim; Bielack, Stefan S.; Borkhardt, Arndt; Brecht, Ines B.; Burkhardt, Birgit; Calaminus, Gabriele; Debatin, Klaus-Michael; Deubzer, Hedwig; Dirksen, Uta; Eckert, Cornelia; Eggert, Angelika; Erlacher, Miriam; et al. (American Journal of Medical Genetics Part A, 2017)
Heritable predisposition is an important cause of cancer in children and adolescents. Although a large number of cancer predisposition genes and their associated syndromes and malignancies have already been described, it appears likely that there are more pediatric cancer patients in whom heritable cancer predisposition syndromes have yet to be recognized. In a consensus meeting in the beginning of 2016, we convened experts in Human Genetics and Pediatric Hematology/Oncology to review the available data, to categorize the large amount of information, and to develop recommendations regarding when a cancer predisposition syndrome should be suspected in a young oncology patient. This review summarizes the current knowledge of cancer predisposition syndromes in pediatric oncology and provides essential information on clinical situations in which a childhood cancer predisposition syndrome should be suspected.
EVALuna2:9370

Chromatin-Remodeling-Factor ARID1B Represses Wnt/?-Catenin Signaling - Vasileiou, Georgia; Ekici, Arif Bülent; Urebe, Steffen; Zweier, Christiane; Hoyer, Juliane; Engels, Hartmut; Behrens, Jürgen; Reis, André; Hadjihannas, Michel (American Journal of Human Genetics, 2015)
The link of chromatin remodeling to both neurodevelopment and cancer has recently been highlighted by the identification of mutations affecting BAF chromatin-remodeling components, such as ARID1B, in individuals with intellectual disability and cancer. However, the underlying molecular mechanism(s) remains unknown. Here, we show that ARID1B is a repressor of Wnt/?-catenin signaling. Through whole-transcriptome analysis, we find that in individuals with intellectual disability and ARID1B loss-of-function mutations, Wnt/?-catenin target genes are upregulated. Using cellular models of low and high Wnt/?-catenin activity, we demonstrate that knockdown of ARID1B activates Wnt/?-catenin target genes and Wnt/?-catenin-dependent transcriptional reporters in a ?-catenin-dependent manner. Reciprocally, forced expression of ARID1B inhibits Wnt/?-catenin signaling downstream of the ?-catenin destruction complex. Both endogenous and exogenous ARID1B associate with ?-catenin and repress Wnt/?-catenin-mediated transcription through the BAF core subunit BRG1. Accordingly, mutations in ARID1B leading to partial or complete deletion of its BRG1-binding domain, as is often observed in intellectual disability and cancers, compromise association with ?-catenin, and the resultant ARID1B mutant proteins fail to suppress Wnt/?-catenin signaling. Finally, knockdown of ARID1B in mouse neuroblastoma cells leads to neurite outgrowth through ?-catenin. The data suggest that aberrations in chromatin-remodeling factors, such as ARID1B, might contribute to neurodevelopmental abnormalities and cancer through deregulation of developmental and oncogenic pathways, such as the Wnt/?-catenin signaling pathway.
EVALuna2:9258

Cost effectiveness of bilateral risk-reducing mastectomy and salpingo-oophorectomy - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Csorba, Roland; Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (European Journal of Medical Research, 2019)
BACKGROUND: Growing demand for risk-reducing surgery in individuals with inherited susceptibility to cancer leads to the question whether these procedures are cost effective for the executing hospitals. This study compared the clinical costs for bilateral risk-reducing mastectomy (BRRM) with and without different types of reconstruction, risk-reducing salpingo-oophorectomy (RRSO), and their combinations with corresponding reimbursements in the statutory health-care system in Germany. PATIENTS AND METHODS: Real total costs of care for BRRM with and without reconstruction, RRSO, and their combinations were calculated as the sum of all personnel and technical costs. These costs calculated in a German University hospital were compared with the sum of all reimbursements in the German DRG-based health-care system. RESULTS: While sole RRSO, BRRM without reconstruction, and BRRM with secondary DIEP (deep inferior epigastric perforator)-reconstruction still result in a small benefit, we even found shortfalls for the hospital with all other prophylactic operations under consideration. The calculated deficits were especially high for BRRM with implant-based breast reconstruction and for combined operations when the risk reduction is achieved with a minimum of separate operations. CONCLUSIONS: Risk-reducing surgery in BRCA-mutation carriers is frequently not cost-covering for the executing hospitals in the German health-care system. Thus, appropriate concepts are required to ensure a nationwide care.
CRIS-Team Scopus Importer:2019-09-24
Keywords: BRCA; Breast cancer; Cost effectiveness; Genetic counseling; Ovarian cancer

Cost-effectiveness of risk-reducing surgeries in preventing hereditary breast and ovarian cancer - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Wiesmann da Silva Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (BREAST, 2017)
Risk-reducing surgeries are a feasible option for mitigating the risk in individuals with inherited susceptibility to cancer, but are the procedures cost-effective in the current health-care system in Germany? This study compared the health-care costs for bilateral risk-reducing mastectomy (BRRM) and risk-reducing (bilateral) salpingo-oophorectomy (RRSO) with cancer treatment costs that could potentially be prevented.The analysis is based on interdisciplinary consultations with individuals with a high familial risk for breast and ovarian cancer at the University Breast Center for Franconia (Germany) between 2009 and 2013 (370 consultations; 44 patients with BRCA1 mutations and 26 with BRCA2 mutations). Health-care costs for risk-reducing surgeries in BRCA mutation carriers were calculated as reimbursements in the German diagnosis-related groups (DRG) hospital pricing system. These costs for the health-care system were compared with the potential cancer treatment costs that could possibly be prevented by risk-reducing surgeries.Long-term health-care costs can be reduced by risk-reducing surgeries after genetic testing in BRCA mutation carriers. The health-care system in Germany would have saved EUR 136,295 if BRRM had been performed and EUR 791,653 if RRSO had been performed before the development of cancer in only 50% of the 70 mutation carriers seen in our center. Moreover, in patients with combined RRSO and BRRM (without breast reconstruction), one further life-year for a 40-year-old BRCA mutation carrier would cost EUR 2,183.Intensive care, including risk-reducing surgeries in BRCA mutation carriers, is cost-effective from the point of view of the health-care system in Germany.
EVALuna2:9369

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder - Mirzaa, Ghayda M.; Chong, Jessica X.; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A.; Sajan, Samin A.; Tang, Sha; et al. (Genetics in Medicine, 2019)
Purpose: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). Methods: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype–phenotype relationships. Results: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. Conclusion: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
CRIS-Team Scopus Importer:2019-11-26
Keywords: autism spectrum disorders; exome sequencing; intellectual disability; next-generation sequencing; ZNF292

De novo missense mutations in the NAA10 gene cause severe non-syndromic developmental delay in males and females - Popp, Bernt; Stove, Svein I.; Endele, Sabine; Myklebust, Line M.; Hoyer, Juliane; Sticht, Heinrich; Azzarello-Burri, Silvia; Rauch, Anita; Arnesen, Thomas; Reis, André (European journal of human genetics, 2015)
Recent studies revealed the power of whole-exome sequencing to identify mutations in sporadic cases with non-syndromic intellectual disability. We now identified de novo missense variants in NAA10 in two unrelated individuals, a boy and a girl, with severe global developmental delay but without any major dysmorphism by trio whole-exome sequencing. Both de novo variants were predicted to be deleterious, and we excluded other variants in this gene. This X-linked gene encodes N-alpha-acetyltransferase 10, the catalytic subunit of the NatA complex involved in multiple cellular processes. A single hypomorphic missense variant p.(Ser37Pro) was previously associated with Ogden syndrome in eight affected males from two different families. This rare disorder is characterized by a highly recognizable phenotype, global developmental delay and results in death during infancy. In an attempt to explain the discrepant phenotype, we used in vitro N-terminal acetylation assays which suggested that the severity of the phenotype correlates with the remaining catalytic activity. The variant in the Ogden syndrome patients exhibited a lower activity than the one seen in the boy with intellectual disability, while the variant in the girl was the most severe exhibiting only residual activity in the acetylation assays used. We propose that N-terminal acetyltransferase deficiency is clinically heterogeneous with the overall catalytic activity determining the phenotypic severity.
EVALuna2:9247

De novo mutations in the genome organizer CTCF cause intellectual disability - Gregor, Anne; Oti, Martin; Kouwenhoven, Evelyn N.; Hoyer, Juliane; Sticht, Heinrich; Ekici, Arif Bülent; Kjaergaard, Susanne; Rauch, Anita; Stunnenberg, Hendrik G.; Uebe, Steffen; Vasileiou, Georgia; Reis, André; et al. (American Journal of Human Genetics, 2013)
An increasing number of genes involved in chromatin structure and epigenetic regulation has been implicated in a variety of developmental disorders, often including intellectual disability. By trio exome sequencing and subsequent mutational screening we now identified two de novo frameshift mutations and one de novo missense mutation in CTCF in individuals with intellectual disability, microcephaly, and growth retardation. Furthermore, an individual with a larger deletion including CTCF was identified. CTCF (CCCTC-binding factor) is one of the most important chromatin organizers in vertebrates and is involved in various chromatin regulation processes such as higher order of chromatin organization, enhancer function, and maintenance of three-dimensional chromatin structure. Transcriptome analyses in all three individuals with point mutations revealed deregulation of genes involved in signal transduction and emphasized the role of CTCF in enhancer-driven expression of genes. Our findings indicate that haploinsufficiency of CTCF affects genomic interaction of enhancers and their regulated gene promoters that drive developmental processes and cognition.
EVALuna2:9184

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Diagnostic Yield and Novel Candidate Genes by Exome Sequencing in 152 Consanguineous Families With Neurodevelopmental Disorders - Reuter, Miriam; Tawamie, Hasan; Buchert, Rebecca; Gebril, Ola Hosny; Froukh, Tawfiq; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Zweier, Christiane; Hoyer, Juliane; Eberlein, Karolin; et al. (JAMA Psychiatry, 2017)
Autosomal recessive inherited neurodevelopmental disorders are highly heterogeneous, and many, possibly most, of the disease genes are still unknown.To promote the identification of disease genes through confirmation of previously described genes and presentation of novel candidates and provide an overview of the diagnostic yield of exome sequencing in consanguineous families.Autozygosity mapping in families and exome sequencing of index patients were performed in 152 consanguineous families (the parents descended from a same ancestor) with at least 1 offspring with intellectual disability (ID). The study was conducted from July 1, 2008, to June 30, 2015, and data analysis was conducted from July 1, 2015, to August 31, 2016.Of the 152 consanguineous families enrolled, 1 child (in 45 families [29.6%]) or multiple children (107 families [70.4%]) had ID; additional features were present in 140 of the families (92.1%). The mean (SD) age of the children was 10.3 (9.0) years, and 171 of 297 (57.6%) were male. In 109 families (71.7%), potentially protein-disrupting and clinically relevant variants were identified. Of these, a clear clinical genetic diagnosis was made in 56 families (36.8%) owing to 57 (likely) pathogenic variants in 50 genes already established in neurodevelopmental disorders (46 autosomal recessive, 2 X-linked, and 2 de novo) or in 7 previously proposed recessive candidates. In 5 of these families, potentially treatable disorders were diagnosed (mutations in PAH, CBS, MTHFR, CYP27A1, and HIBCH), and in 1 family, 2 disease-causing homozygous variants in different genes were identified. In another 48 families (31.6%), 52 convincing recessive variants in candidate genes that were not previously reported in regard to neurodevelopmental disorders were identified. Of these, 14 were homozygous and truncating in GRM7, STX1A, CCAR2, EEF1D, GALNT2, SLC44A1, LRRIQ3, AMZ2, CLMN, SEC23IP, INIP, NARG2, FAM234B, and TRAP1. The diagnostic yield was higher in individuals with severe ID (35 of 77 [45.5%]), in multiplex families (42 of 107 [39.3%]), in patients with additional features (30 of 70 [42.9%]), and in those with remotely related parents (15 of 34 [44.1%]).Because of the high diagnostic yield of 36.8% and the possibility of identifying treatable diseases or the coexistence of several disease-causing variants, using exome sequencing as a first-line diagnostic approach in consanguineous families with neurodevelopmental disorders is recommended. Furthermore, the literature is enriched with 52 convincing candidate genes that are awaiting confirmation in independent families.
EVALuna2:9388

DLG4-related synaptopathy: a new rare brain disorder - Rodriguez-Palmero, Agusti; Boerrigter, Melissa Maria; Gomez-Andres, David; Aldinger, Kimberly A.; Marcos-Alcalde, Inigo; Popp, Bernt; Everman, David B.; Lovgren, Alysia Kern; Arpin, Stephanie; Bahrambeigi, Vahid; Beunders, Gea; Bisgaard, Anne-Marie; et al. (Genetics in Medicine, 2021)
Purpose: Postsynaptic density protein-95 (PSD-95), encoded by DLG4, regulates excitatory synaptic function in the brain. Here we present the clinical and genetic features of 53 patients (42 previously unpublished) with DLG4 variants. Methods: The clinical and genetic information were collected through GeneMatcher collaboration. All the individuals were investigated by local clinicians and the gene variants were identified by clinical exome/genome sequencing. Results: The clinical picture was predominated by early onset global developmental delay, intellectual disability, autism spectrum disorder, and attention deficit–hyperactivity disorder, all of which point to a brain disorder. Marfanoid habitus, which was previously suggested to be a characteristic feature of DLG4-related phenotypes, was found in only nine individuals and despite some overlapping features, a distinct facial dysmorphism could not be established. Of the 45 different DLG4 variants, 39 were predicted to lead to loss of protein function and the majority occurred de novo (four with unknown origin). The six missense variants identified were suggested to lead to structural or functional changes by protein modeling studies. Conclusion: The present study shows that clinical manifestations associated with DLG4 overlap with those found in other neurodevelopmental disorders of synaptic dysfunction; thus, we designate this group of disorders as DLG4-related synaptopathy. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05

Eight further individuals with intellectual disability and epilepsy carrying bi-allelic CNTNAP2 aberrations allow delineation of the mutational and phenotypic spectrum - Smogavec, Mateja; Cleall, Alison; Hoyer, Juliane; Lederer, Damien; Nassogne, Marie-Cecile; Palmer, Elizabeth E.; Deprez, Marie; Benoit, Valerie; Maystadt, Isabelle; Noakes, Charlotte; Leal-Esquivel, Alejandro; Shaw, Marie; et al. (Journal of Medical Genetics, 2016)
Heterozygous copy number variants (CNVs) or sequence variants in the contactin-associated protein 2 gene CNTNAP2 have been discussed as risk factors for a wide spectrum of neurodevelopmental and neuropsychiatric disorders. Bi-allelic aberrations in this gene are causative for an autosomal-recessive disorder with epilepsy, severe intellectual disability (ID) and cortical dysplasia (CDFES). As the number of reported individuals is still limited, we aimed at a further characterisation of the full mutational and clinical spectrum.Targeted sequencing, chromosomal microarray analysis or multigene panel sequencing was performed in individuals with severe ID and epilepsy.We identified homozygous mutations, compound heterozygous CNVs or CNVs and mutations in CNTNAP2 in eight individuals from six unrelated families. All aberrations were inherited from healthy, heterozygous parents and are predicted to be deleterious for protein function. Epilepsy occurred in all affected individuals with onset in the first 3.5 years of life. Further common aspects were ID (severe in 6/8), regression of speech development (5/8) and behavioural anomalies (7/8). Interestingly, cognitive impairment in one of two affected brothers was, in comparison, relatively mild with good speech and simple writing abilities. Cortical dysplasia that was previously reported in CDFES was not present in MRIs of six individuals and only suspected in one.By identifying novel homozygous or compound heterozygous, deleterious CNVs and mutations in eight individuals from six unrelated families with moderate-to-severe ID, early onset epilepsy and behavioural anomalies, we considerably broaden the mutational and clinical spectrum associated with bi-allelic aberrations in CNTNAP2.
EVALuna2:9347

Exome Pool-Seq in neurodevelopmental disorders - Popp, Bernt; Ekici, Arif Bülent; Thiel, Christian; Hoyer, Juliane; Wiesener, Antje; Kraus, Cornelia; Reis, André; Zweier, Christiane (European journal of human genetics, 2017)
High throughput sequencing has greatly advanced disease gene identification, especially in heterogeneous entities. Despite falling costs this is still an expensive and laborious technique, particularly when studying large cohorts. To address this problem we applied Exome Pool-Seq as an economic and fast screening technology in neurodevelopmental disorders (NDDs). Sequencing of 96 individuals can be performed in eight pools of 12 samples on less than one Illumina sequencer lane. In a pilot study with 96 cases we identified 27 variants, likely or possibly affecting function. Twenty five of these were identified in 923 established NDD genes (based on SysID database, status November 2016) (ACTB, AHDC1, ANKRD11, ATP6V1B2, ATRX, CASK, CHD8, GNAS, IFIH1, KCNQ2, KMT2A, KRAS, MAOA, MED12, MED13L, RIT1, SETD5, SIN3A, TCF4, TRAPPC11, TUBA1A, WAC, ZBTB18, ZMYND11), two in 543 (SysID) candidate genes (ZNF292, BPTF), and additionally a de novo loss-of-function variant in LRRC7, not previously implicated in NDDs. Most of them were confirmed to be de novo, but we also identified X-linked or autosomal-dominantly or autosomal-recessively inherited variants. With a detection rate of 28%, Exome Pool-Seq achieves comparable results to individual exome analyses but reduces costs by >85%. Compared with other large scale approaches using Molecular Inversion Probes (MIP) or gene panels, it allows flexible re-analysis of data. Exome Pool-Seq is thus well suited for large-scale, cost-efficient and flexible screening in characterized but heterogeneous entities like NDDs.
EVALuna2:9387

Ex Vivo Chromosomal Radiosensitivity Testing in Patients with Pathological Germline Variants in Breast Cancer High-Susceptibility Genes BReast CAncer 1 and BReast CAncer 2 - Zuhair Kassem, Tara; Wunderle, Marius; Kuhlmann, Lukas; Rübner, Matthias; Hübner, Hanna; Hoyer, Juliane; Reis, André; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Current Issues in Molecular Biology, 2023)
Background: Individual radiosensitivity is an important factor in the occurrence of undesirable consequences of radiotherapy. The potential for increased radiosensitivity has been linked to highly penetrant heterozygous mutations in DNA repair genes such as BRCA1 and BRCA2. By studying the chromosomal radiosensitivity of BRCA1/2 mutation carriers compared to the general population, we study whether increased chromosomal radiation sensitivity is observed in patients with BRCA1/2 variants. Methods: Three-color-fluorescence in situ hybridization was performed on ex vivo-irradiated peripheral blood lymphocytes from 64 female patients with a heterozygous germline BRCA1 or BRCA2 mutation. Aberrations in chromosomes #1, #2 and #4 were analyzed. Mean breaks per metaphase (B/M) served as the parameter for chromosomal radiosensitivity. The results were compared with chromosomal radiosensitivity in a cohort of generally healthy individuals and patients with rectal cancer or breast cancer. Results: Patients with BRCA1/2 mutations (n = 64; B/M 0.47) overall showed a significantly higher chromosomal radiosensitivity than general healthy individuals (n = 211; B/M 0.41) and patients with rectal cancer (n = 379; B/M 0.44) and breast cancer (n = 147; B/M 0.45) without proven germline mutations. Chromosomal radiosensitivity varied depending on the locus of the BRCA1/2 mutation. Conclusions: BRCA1/2 mutations result in slightly increased chromosomal sensitivity to radiation. A few individual patients have a marked increase in radiation sensitivity. Therefore, these patients are at a higher risk for adverse therapeutic consequences.
CRIS-Team Scopus Importer:2023-09-08
Keywords: BRCA1; BRCA2; breast cancer; chromosomal radiosensitivity; FISH assay; radiation oncology; radiation sensitivity testing; radiotherapy

Familial acute aortic dissection associated with a novel ACTA2 germline variant - Strecker, Thomas; Wiesmueller, Felix; Rudnik-Schoeneborn, Sabine; Hoyer, Juliane; Wiesmann da Silva Reis, André; Weyand, Michael; Agaimy, Abbas (Virchows Archiv, 2022)
Aortic dissection is a life-threatening cardiovascular disease. Hereditary disorders are responsible for a small percentage of cases. Nonetheless, it is important to identify genetic causes, as they are often autosomal dominantly inherited and are of life-saving importance if we can identify persons at risk. Mutations of the ACTA2 gene are the most common cause of non-syndromic familial aortic disease. Exploration of the genetic background in suspected familial cases and determination of the exact etiology are mandatory for management and establishing appropriate follow-up strategies due to the risk of fatal recurrences. Herein, we present a 21-year-old male with a familial acute aortic dissection associated with novel ACTA2 germline variant and discuss the management and surveillance considerations.
CRIS-Team WoS Importer:2022-08-05

Gene panel sequencing in familial breast/ovarian cancer patients identifies multiple novel mutations also in genes others than BRCA1/2 - Kraus, Cornelia; Hoyer, Juliane; Vasileiou, Georgia; Wunderle, Marius; Lux, Michael P.; Fasching, Peter; Krumbiegel, Mandy; Uebe, Steffen; Reuter, Miriam; Beckmann, Matthias; Reis, André (International Journal of Cancer, 2017)
Breast and ovarian cancer (BC/OC) predisposition has been attributed to a number of high- and moderate to low-penetrance susceptibility genes. With the advent of next generation sequencing (NGS) simultaneous testing of these genes has become feasible. In this monocentric study, we report results of panel-based screening of 14 BC/OC susceptibility genes (BRCA1, BRCA2, RAD51C, RAD51D, CHEK2, PALB2, ATM, NBN, CDH1, TP53, MLH1, MSH2, MSH6 and PMS2) in a group of 581 consecutive individuals from a German population with BC and/or OC fulfilling diagnostic criteria for BRCA1 and BRCA2 testing including 179 with a triple-negative tumor. Altogether we identified 106 deleterious mutations in 105 (18%) patients in 10 different genes, including seven different exon deletions. Of these 106 mutations, 16 (15%) were novel and only six were found in BRCA1/2. To further characterize mutations located in or nearby splicing consensus sites we performed RT-PCR analysis which allowed confirmation of pathogenicity in 7 of 9 mutations analyzed. In PALB2, we identified a deleterious variant in six cases. All but one were associated with early onset BC and a positive family history indicating that penetrance for PALB2 mutations is comparable to BRCA2. Overall, extended testing beyond BRCA1/2 identified a deleterious mutation in further 6% of patients. As a downside, 89 variants of uncertain significance were identified highlighting the need for comprehensive variant databases. In conclusion, panel testing yields more accurate information on genetic cancer risk than assessing BRCA1/2 alone and wide-spread testing will help improve penetrance assessment of variants in these risk genes.
EVALuna2:9340

Genetic and neurodevelopmental spectrum of SYNGAP1-associated intellectual disability and epilepsy - Mignot, Cyril; Von Stuelpnagel, Celina; Nava, Caroline; Ville, Dorothee; Sanlaville, Damien; Lesca, Gaetan; Rastetter, Agnes; Gachet, Benoit; Marie, Yannick; Korenke, G. Christoph; Borggraefe, Ingo; Hoffmann-Zacharska, Dorota; et al. (Journal of Medical Genetics, 2016)
We aimed to delineate the neurodevelopmental spectrum associated with SYNGAP1 mutations and to investigate genotype-phenotype correlations.We sequenced the exome or screened the exons of SYNGAP1 in a total of 251 patients with neurodevelopmental disorders. Molecular and clinical data from patients with SYNGAP1 mutations from other centres were also collected, focusing on developmental aspects and the associated epilepsy phenotype. A review of SYNGAP1 mutations published in the literature was also performed.We describe 17 unrelated affected individuals carrying 13 different novel loss-of-function SYNGAP1 mutations. Developmental delay was the first manifestation of SYNGAP1-related encephalopathy; intellectual disability became progressively obvious and was associated with autistic behaviours in eight patients. Hypotonia and unstable gait were frequent associated neurological features. With the exception of one patient who experienced a single seizure, all patients had epilepsy, characterised by falls or head drops due to atonic or myoclonic seizures, (myoclonic) absences and/or eyelid myoclonia. Triggers of seizures were frequent (n=7). Seizures were pharmacoresistant in half of the patients. The severity of the epilepsy did not correlate with the presence of autistic features or with the severity of cognitive impairment. Mutations were distributed throughout the gene, but spared spliced 3' and 5' exons. Seizures in patients with mutations in exons 4-5 were more pharmacoresponsive than in patients with mutations in exons 8-15.SYNGAP1 encephalopathy is characterised by early neurodevelopmental delay typically preceding the onset of a relatively recognisable epilepsy comprising generalised seizures (absences, myoclonic jerks) and frequent triggers.
EVALuna2:9321

Haploinsufficiency of the Chromatin Remodeler BPTF Causes Syndromic Developmental and Speech Delay, Postnatal Microcephaly, and Dysmorphic Features - Stankiewicz, Pawel; Khan, Tahir N.; Szafranski, Przemyslaw; Slattery, Leah; Streff, Haley; Vetrini, Francesco; Bernstein, Jonathan A.; Brown, Chester W.; Rosenfeld, Jill A.; Rednam, Surya; Scollon, Sarah; Bergstrom, Katie L.; et al. (American Journal of Human Genetics, 2017)
Bromodomain PHD finger transcription factor (BPTF) is the largest subunit of nucleosome remodeling factor (NURF), a member of the ISWI chromatin-remodeling complex. However, the clinical consequences of disruption of this complex remain largely uncharacterized. BPTF is required for anterior-posterior axis formation of the mouse embryo and was shown to promote posterior neuroectodermal fate by enhancing Smad2-activated wnt8 expression in zebrafish. Here, we report eight loss-of-function and two missense variants (eight de novo and two of unknown origin) in BPTF on 17q24.2. The BPTF variants were found in unrelated individuals aged between 2.1 and 13 years, who manifest variable degrees of developmental delay/intellectual disability (10/10), speech delay (10/10), postnatal microcephaly (7/9), and dysmorphic features (9/10). Using CRISPR-Cas9 genome editing of bptf in zebrafish to induce a loss of gene function, we observed a significant reduction in head size of F0 mutants compared to control larvae. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and phospho-histone H3 (PH3) staining to assess apoptosis and cell proliferation, respectively, showed a significant increase in cell death in F0 mutants compared to controls. Additionally, we observed a substantial increase of the ceratohyal angle of the craniofacial skeleton in bptf F0 mutants, indicating abnormal craniofacial patterning. Taken together, our data demonstrate the pathogenic role of BPTF haploinsufficiency in syndromic neurodevelopmental anomalies and extend the clinical spectrum of human disorders caused by ablation of chromatin remodeling complexes.
EVALuna2:9361

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Psychiatric Disorders and Distal 21q Deletion-A Case Report - Briegel, Wolfgang; Hoyer, Juliane (International Journal of Environmental Research and Public Health, 2020)
Partial deletion of chromosome 21q is a very rare genetic condition with highly variable phenotypic features including heart defects, high or cleft palate, brain malformations (e.g., cerebral atrophy), developmental delay and intellectual disability. So far, there is very limited knowledge about psychiatric disorders and their effective treatment in this special population. To fill this gap, the authors present the case of an initially five-year-old girl with distal deletion (del21q22.2) and comorbid oppositional defiant disorder (main psychiatric diagnosis) covering a period of time of almost four years comprising initial psychological/psychiatric assessment, subsequent treatment with Parent-Child Interaction Therapy (PCIT), and follow-up assessments. Post-intervention results including a 19-month follow-up indicated good overall efficacy of PCIT and high parental satisfaction with the treatment. This case report makes a substantial contribution to enhancing knowledge on psychiatric comorbidity and its effective treatment in patients with terminal 21q deletion. Moreover, it emphasizes the necessity of multidisciplinarity in diagnosis and treatment due to the variety of anomalies associated with 21q deletion. Regular screenings for psychiatric disorders and (if indicated) thorough psychological and psychiatric assessment seem to be reasonable in most affected children, as children with developmental delays are at increased risk of developing psychiatric disorders. As demonstrated with this case report, PCIT seems to be a good choice to effectively reduce disruptive behaviors in young children with partial deletion of chromosome 21q.
CRIS-Team Scopus Importer:2020-05-15
Keywords: 21q22.2-q22.3; attention deficit/hyperactivity disorder; case report; chromosome 21; distal deletion; oppositional defiant disorder; Parent–Child Interaction Therapy (PCIT)

Risk, Prediction and Prevention of Hereditary Breast Cancer - Large-Scale Genomic Studies in Times of Big and Smart Data - Wunderle, Marius; Olmes, Gregor; Nabieva, Naiba; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Hack, Carolin; Erber, Ramona; Ekici, Arif Bülent; Hoyer, Juliane; Vasileiou, Georgia; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Over the last two decades genetic testing for mutations in BRCA1 and BRCA2 has become standard of care for women and men who are at familial risk for breast or ovarian cancer. Currently, genetic testing more often also includes so-called panel genes, which are assumed to be moderate-risk genes for breast cancer. Recently, new large-scale studies provided more information about the risk estimation of those genes. The utilization of information on panel genes with regard to their association with the individual breast cancer risk might become part of future clinical practice. Furthermore, large efforts have been made to understand the influence of common genetic variants with a low impact on breast cancer risk. For this purpose, almost 450 000 individuals have been genotyped for almost 500 000 genetic variants in the OncoArray project. Based on first results it can be assumed that - together with previously identified common variants - more than 170 breast cancer risk single nucleotide polymorphisms can explain up to 18% of familial breast cancer risk. The knowledge about genetic and non-genetic risk factors and its implementation in clinical practice could especially be of use for individualized prevention. This includes an individualized risk prediction as well as the individualized selection of screening methods regarding imaging and possible lifestyle interventions. The aim of this review is to summarize the most recent developments in this area and to provide an overview on breast cancer risk genes, risk prediction models and their utilization for the individual patient.
EVALuna2:34612

Spliceosome malfunction causes neurodevelopmental disorders with overlapping features - Li, Dong; Wang, Qin; Bayat, Allan; Battig, Mark R.; Zhou, Yijing; Bosch, Daniëlle G.M.; van Haaften, Gijs; Granger, Leslie; Petersen, Andrea K.; Pérez-Jurado, Luis A.; Aznar-Laín, Gemma; Aneja, Anushree; et al. (Journal of Clinical Investigation, 2024)
Pre-mRNA splicing is a highly coordinated process. While its dysregulation has been linked to neurological deficits, our understanding of the underlying molecular and cellular mechanisms remains limited. We implicated pathogenic variants in U2AF2 and PRPF19, encoding spliceosome subunits in neurodevelopmental disorders (NDDs), by identifying 46 unrelated individuals with 23 de novo U2AF2 missense variants (including 7 recurrent variants in 30 individuals) and 6 individuals with de novo PRPF19 variants. Eight U2AF2 variants dysregulated splicing of a model substrate. Neuritogenesis was reduced in human neurons differentiated from human pluripotent stem cells carrying two U2AF2 hyper-recurrent variants. Neural loss of function (LoF) of the Drosophila orthologs U2af50 and Prp19 led to lethality, abnormal mushroom body (MB) patterning, and social deficits, which were differentially rescued by wild-type and mutant U2AF2 or PRPF19. Transcriptome profiling revealed splicing substrates or effectors (including Rbfox1, a third splicing factor), which rescued MB defects in U2af50deficient flies. Upon reanalysis of negative clinical exomes followed by data sharing, we further identified 6 patients with NDD who carried RBFOX1 missense variants which, by in vitro testing, showed LoF. Our study implicates 3 splicing factors as NDD-causative genes and establishes a genetic network with hierarchy underlying human brain development and function.
CRIS-Team Scopus Importer:2024-01-19

Surveillance recommendations for DICER1 pathogenic variant carriers: a report from the SIOPE Host Genome Working Group and CanGene-CanVar Clinical Guideline Working Group - Bakhuizen, Jette J.; Hanson, Helen; Van De Tuin, Karin; Lalloo, Fiona; Tischkowitz, Marc; Wadt, Karin; Doergeloh, Beate B.; Farah, Roula A.; Glentis, Stavros; Golmard, Lisa; Hoyer, Juliane; Jahnukainen, Kirsi; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Targeted sequencing of FH-deficient uterine leiomyomas reveals biallelic inactivating somatic fumarase variants and allows characterization of missense variants - Popp, Bernt; Erber, Ramona; Kraus, Cornelia; Vasileiou, Georgia; Hoyer, Juliane; Burghaus, Stefanie; Hartmann, Arndt; Beckmann, Matthias; Reis, André; Agaimy, Abbas (Modern Pathology, 2020)
Uterine leiomyomas (ULs) constitute a considerable health burden in the general female population. The fumarate hydratase (FH) deficient subtype is found in up to 1.6% and can occur in hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome. We sequenced 13 FH deficient ULs from a previous immunohistochemical screen using a targeted panel and identified biallelic FH variants in all. In eight, we found an FH point mutation (two truncating, six missense) with evidence for loss of the second allele. Variant allele-frequencies in all cases with a point mutation pointed to somatic variants. Spatial clustering of the identified missense variants in the lyase domain indicated altered fumarase oligomerization with subsequent degradation as explanation for the observed FH deficiency. Biallelic FH deletions in five tumors confirm the importance of copy number loss as mutational mechanism. By curating all pathogenic FH variants and calculating their population frequency, we estimate a carrier frequency of up to 1/2,563. Comparing with the prevalence of FH deficient ULs, we conclude that most are sporadic and estimate 2.7–13.9% of females with an FH deficient UL to carry a germline FH variant. Further prospective tumor/normal sequencing studies are needed to develop a reliable screening strategy for HLRCC in women with ULs.
CRIS-Team Scopus Importer:2020-07-10

TRIM28 haploinsufficiency predisposes to Wilms tumor - Diets, Illja J.; Hoyer, Juliane; Ekici, Arif Bülent; Popp, Bernt; Hoogerbrugge, Nicoline; van Reijmersdal, Simon V.; Bhaskaran, Rajith; Hadjihannas, Michel; Vasileiou, Georgia; Thiel, Christian; Seven, Didem; Uebe, Steffen; et al. (International Journal of Cancer, 2019)
Two percent of patients with Wilms tumors have a positive family history. In many of these cases the genetic cause remains unresolved. By applying germline exome sequencing in two families with two affected individuals with Wilms tumors, we identified truncating mutations in TRIM28. Subsequent mutational screening of germline and tumor DNA of 269 children affected by Wilms tumor was performed, and revealed seven additional individuals with germline truncating mutations, and one individual with a somatic truncating mutation in TRIM28. TRIM28 encodes a complex scaffold protein involved in many different processes, including gene silencing, DNA repair and maintenance of genomic integrity. Expression studies on mRNA and protein level showed reduction of TRIM28, confirming a loss-of-function effect of the mutations identified. The tumors showed an epithelial-type histology that stained negative for TRIM28 by immunohistochemistry. The tumors were bilateral in six patients, and 10/11 tumors are accompanied by perilobar nephrogenic rests. Exome sequencing on eight tumor DNA samples from six individuals showed loss-of-heterozygosity (LOH) of the TRIM28-locus by mitotic recombination in seven tumors, suggesting that TRIM28 functions as a tumor suppressor gene in Wilms tumor development. Additionally, the tumors showed very few mutations in known Wilms tumor driver genes, suggesting that loss of TRIM28 is the main driver of tumorigenesis. In conclusion, we identified heterozygous germline truncating mutations in TRIM28 in 11 children with mainly epithelial-type Wilms tumors, which become homozygous in tumor tissue. These data establish TRIM28 as a novel Wilms tumor predisposition gene, acting as a tumor suppressor gene by LOH.
CRIS-Team Scopus Importer:2019-05-02
Keywords: genetic predisposition; haploinsufficiency; TRIM28; Wilms tumor

Variants in LRRC7 lead to intellectual disability, autism, aggression and abnormal eating behaviors - Willim, Jana; Woike, Daniel; Greene, Daniel; Das, Sarada; Pfeifer, Kevin; Yuan, Weimin; Lindsey, Anika; Itani, Omar; Böhme, Amber L.; Tibbe, Debora; Hönck, Hans Hinrich; Hassani Nia, Fatemeh; et al. (Nature Communications, 2024)
Members of the leucine rich repeat (LRR) and PDZ domain (LAP) protein family are essential for animal development and histogenesis. Densin-180, encoded by LRRC7, is the only LAP protein selectively expressed in neurons. Densin-180 is a postsynaptic scaffold at glutamatergic synapses, linking cytoskeletal elements with signalling proteins such as the α-subunit of Ca2+/calmodulin-dependent protein kinase II. We have previously observed an association between high impact variants in LRRC7 and Intellectual Disability; also three individual cases with variants in LRRC7 had been described. We identify here 33 individuals (one of them previously described) with a dominant neurodevelopmental disorder due to heterozygous missense or loss-of-function variants in LRRC7. The clinical spectrum involves intellectual disability, autism, ADHD, aggression and, in several cases, hyperphagia-associated obesity. A PDZ domain variant interferes with synaptic targeting of Densin-180 in primary cultured neurons. Using in vitro systems (two hybrid, BioID, coimmunoprecipitation of tagged proteins from 293T cells) we identified new candidate interaction partners for the LRR domain, including protein phosphatase 1 (PP1), and observed that variants in the LRR reduced binding to these proteins. We conclude that LRRC7 encodes a major determinant of intellectual development and behaviour.
CRIS-Team Scopus Importer:2024-11-22